1993
DOI: 10.1159/000292584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Maternal Glucose Metabolism

Abstract: Maternal smoking, studied in late pregnancy, was found to be associated with lower blood glucose values, both during fasting and after an intravenous glucose load. As a correlation between blood glucose levels and infant birth weight has been reported, it is possible that smoking during pregnancy might reduce fetal growth through an effect on maternal glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Recent studies have suggested defects in both placental size (22,24) and function with reported alterations in endothelial function, (23,24) epidermal growth factor, (26) and cytotrophoblast differentiation. (27) In support of this hypothesis, we found a decrease in placental weight in smoking mothers, and adjustment for this decrease led to nonsignificant results for smoking, suggesting that placental weight is an intermediate variable for the negative effect of smoking. Furthermore, our results indicate that the deficit is bone mass is partially explicable by low birth weight, but more so by subsequent growth deficits, suggesting that growth, at least during the first 8 years, may be programmed in utero.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Recent studies have suggested defects in both placental size (22,24) and function with reported alterations in endothelial function, (23,24) epidermal growth factor, (26) and cytotrophoblast differentiation. (27) In support of this hypothesis, we found a decrease in placental weight in smoking mothers, and adjustment for this decrease led to nonsignificant results for smoking, suggesting that placental weight is an intermediate variable for the negative effect of smoking. Furthermore, our results indicate that the deficit is bone mass is partially explicable by low birth weight, but more so by subsequent growth deficits, suggesting that growth, at least during the first 8 years, may be programmed in utero.…”
Section: Discussionmentioning
confidence: 52%
“…These include impaired placental size and function, (22)(23)(24)(25)(26) lower maternal glucose levels, (27) deficient maternal diet, (28) and lower volume of maternal breast milk. (29) It would appear most likely that smoking primarily interferes with placental function.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine has been shown to block the release of inflammatory cytokines, inhibiting inflammation associated with insulin resistance and thereby diminishing hyperglycemia [9]. Smoking-induced release of catecholamines may also increase the metabolism of soluble nutrients, thereby lowering glucose levels among smokers [36]. Smoking has also been consistently and negatively associated with pre-eclampsia via physiological mechanisms that may be similar [37].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal-growth retardation may result from a variety of causes, including placental insufficiency, genetic defects and environmental toxins (16,17). Cigarette smoking during pregnancy, a well-documented cause of reduced birthweight, may exert its influence on fetal growth through several mechanisms, such as changes in the protein, fat or glucose metabolism (18), hypoxia secondary to vasoconstriction and impaired placental function, as well as a shift of the fetal oxyhaeinoglobin dissociation curve to the left, leading to reduced ebergy availability (10).…”
Section: Discussionmentioning
confidence: 99%